2017
DOI: 10.1016/j.jneb.2017.05.350
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Evaluation of the You Can Do It Initiative to Promote Exclusive Breastfeeding Among Women Enrolled in the New York State WIC Program by Race/Ethnicity

Abstract: The initiative seems to be effective at increasing exclusive BF, particularly among non-Hispanic black and Hispanic women in the New York State WIC program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…The primary obstacles reported for breastfeeding in this study aligns with results of previous research from the region (12,(18)(19) and other populations (20)(21). Even though they had the option of adding another obstacle that was not listed, all the participants who reported having some di culty with breastfeeding selected one of the 10 options presented.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The primary obstacles reported for breastfeeding in this study aligns with results of previous research from the region (12,(18)(19) and other populations (20)(21). Even though they had the option of adding another obstacle that was not listed, all the participants who reported having some di culty with breastfeeding selected one of the 10 options presented.…”
Section: Discussionsupporting
confidence: 84%
“…There are other studies that have shown the effectiveness of doing counseling focused on the needs of women (27-28). In the Edmunds L. et al (20) study, pre and postnatal counseling was provided to women enrolled in the WIC program. The BAPT instrument was applied to assess what their main problems were and they were given personalized counseling based on that.…”
Section: Discussionmentioning
confidence: 99%
“…that is, receiving encouragement, support, guidance, which highlights the importance of investing in the training and development of these professionals at all levels of care. Preparing health professionals to be able to promote breastfeeding, improving their knowledge, skills, and consequently their professional practice can result in more women having access to adequate breastfeeding counselling, guidance, and management from pregnancy until the termination of breastfeeding, as already pointed out by other authors (Edmunds, Lee, Eldridge, & Sekhobo, 2017;Haroon, Das, Salam, Imdad, & Bhutta, 2013;Jesus, Oliveira, & Moraes, 2017;McFadden et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Successful breastfeeding peer counselor programs such as the You Can Do It (YCDI) initiative im-plemented by WIC clinics is an example of how peers can be used to support adolescent mothers who choose to breastfeed. [39] A meta-analysis review of eleven controlled studies examining exclusive breastfeeding in low and middle-income countries discovered peer support significantly increased exclusive breastfeeding duration. [40] A study of pregnant African American women ages 18 to 45 found the intent to breastfeed doubled after attending WIC breastfeeding peer support programs.…”
Section: Discussionmentioning
confidence: 99%